2002
DOI: 10.1182/blood-2001-12-0360
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct dendritic cell (DC) populations induced by physiologic stimuli: prostaglandin E2 regulates the migratory capacity of specific DC subsets

Abstract: Migration of antigen (Ag)-loaded dendritic cells (DCs) from sites of infection into draining lymphoid tissues is fundamental to the priming of T-cell immune responses. We evaluated monocyte-derived DCs (MoDCs) and peripheral blood DCs (PBDCs) to respond to proinflammatory mediators, CD40L, and intact bacteria. All classes of stimuli induced DC phenotypic maturation. However, for MoDCs, only prostaglandin E 2 (PGE 2 )-containing stimuli induced migratory-type DCs. Thus, immature MoDCs that encountered proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
337
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(363 citation statements)
references
References 73 publications
24
337
2
Order By: Relevance
“…Our data are in agreement with recent findings that showed an enhanced response of dendritic cells to the chemokines SLC and ELC in the presence of PGE 2 without a concomitant enhancement of the expression of the specific chemokine receptor CCR7 [14,15]. In addition, a study by Kurth et al [23] Of note, our data show that PGE 2 exerts its effects on human monocytes independently of chemokine receptor expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are in agreement with recent findings that showed an enhanced response of dendritic cells to the chemokines SLC and ELC in the presence of PGE 2 without a concomitant enhancement of the expression of the specific chemokine receptor CCR7 [14,15]. In addition, a study by Kurth et al [23] Of note, our data show that PGE 2 exerts its effects on human monocytes independently of chemokine receptor expression.…”
Section: Discussionsupporting
confidence: 93%
“…They are members of the family of G protein-coupled receptors and appear to be differentially expressed among inflammatory cells. Recent studies indicate that PGE 2 can modulate the migratory capacity of different cell types, such as endothelial [10,11], mesangial [12], and tumor cells [13] as well as dendritic cells [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Upon maturation, CCR7 expression was induced on MUTZ-3 IDC and MUTZ-3 LC, and this expression was accompanied by responsiveness to LNhoming chemokines CCL19 and CCL21. Interestingly, and unlike migration of MoDC (30,31), migration of MUTZ-3 IDC and MUTZ-3 LC was independent (IDC) or less dependent (LC) on PGE 2 . Importantly, so far it is not clear whether CD34-derived IDC or LC migration is dependent on PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the effect of PGI 2 analogs, PGE 2 has been shown to inhibit IL-12, TNF-␣, and IL-6 production by BMDCs, suppress MHC class II expression, and enhance IL-10 production (22,29,38,39). Studies showed that DCs may be activated to produce high levels of proinflammatory cytokines and remain at sites of inflammation or develop into CCR7-expressing cells that allow them to migrate to the draining lymph nodes and induce Ag-specific immune responses (50,51). These migratory DCs produce low levels of inflammatory cytokines (50).…”
Section: Discussionmentioning
confidence: 99%